Analisi Perilaku Produsen pada UMKM Muslim Kopikuni: Menggunakan Pendekatan Analisis SWOT - Aidil Qontas Hamzah Lubis; Dahrani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to analyze producer behavior, identify internal and external factors using the SWOT approach in Kokukuni Halal MSMEs. The method used in this research uses a qualitative approach to understand producer behavior in Muslim/Halal Kopikuni MSMEs. The results of this research conclude that there is a significant correlation between producer behavior and marketing of Kupikuni products. In relation to the management function, decision making is the act of selecting alternatives. It was found that an effective strategy that can be implemented is to use the SWOT strategy, which uses all the strengths it has to take advantage of existing opportunities. This is because the location is close together, which means it is strategic and the price is more or less the same. Consumer behavior can influence the amount of demand and needs. Producer behavior is the activity of regulating production so that the product produced is of high quality so that it can generate profits. This producer behavior can influence the amount of production and supply of goods or services. Market behavior is the pattern of market habits, including the decision-making process and individual and organizational activities regarding certain products.